Assessment of the causal association between obstructive sleep apnea and telomere length: a bidirectional mendelian randomization study - Xie, Rongfang; Chen, Shiyu; Li, Xiaojian; Lan, Zhihui (Frontiers in Genetics, 2025)
BackgroundA plethora of observational studies has established a significant correlation between Obstructive Sleep Apnea (OSA) and Telomere Length (TL). Nevertheless, a universal consensus on precise causal association and its directionality has not yet been achieved. To shed light on this, we employed Mendelian Randomization (MR) to investigate the bidirectional causal association between OSA and TL.MethodUtilizing publicly accessible Genome-Wide Association Studies (GWAS) datasets, we procured genetic data pertinent to MR analysis. The study incorporated samples from both the OSA (n = 217,955) and TL (n = 472,174) cohorts. In the forward MR analysis, OSA served as the exposure variable and TL as the outcome. Conversely, the reverse MR analysis treated TL as the exposure and OSA as the outcome. We employed the Inverse variance weighted (IVW) as the primary methodology for MR analysis. To ensure the robustness of our MR findings, multiple sensitivity analyses were performed.ResultsIn the forward MR analysis, a negative correlation was indicated between OSA and TL (IVW: odds ratio (OR) = 0.964, 95% confidence interval (CI): 0.939–0.980, P = 0.006 < 0.05). However, no significant association was identified between TL and the risk of OSA in the reverse MR analysis (IVW: OR = 0.965, 95% CI: 0.870–1.070, P = 0.499 > 0.05).ConclusionOur study indicated a potential association between OSA and the increased risk of shorter TL, offering vital academic support for future clinical studies on this association.